A First Record of Metal Fractionation in Coastal Sediment from Ambon Bay, Moluccas, Indonesia - Lestari Lestari; Fitri Budiyanto; Corry Yanti Manullang (Marine Geological Institute of Indonesia, 2019)
Five metals in sediment samples at seven sites from the Ambon Bay were analyzed with BCR sequential extraction procedure to determine chemical fractionation of metals and to assess bioavailability of metals with Risk Assessment Code (RAC). The result showed that the percentages of cadmium (100%), lead (82.6-97.08%) and zinc (41.68-76.33%) were mostly accumulated in the non-residual (F1+F2+F3) fraction of the total concentrations. While the copper percentages (44.74-78.91%) and nickel (59.71-74.16%) were mostly accumulated in residual (F4) fraction of the total concentrations. The Risk Assessment Code (RAC) reveals that cadmium, copper, nickel and zinc at locations exist in acid soluble (exchangeable) fraction and therefore, they are in low until very high risk category meanwhile there is no Pb at locations exist in acid soluble (exchangeable) fraction.